Structural Locus of the pH Gate in the Kir1.1 Inward Rectifier Channel - Sackin, Henry (Biophysical Society, 2005)
The closed-state crystal structure of prokaryotic inward rectifier, KirBac1.1, has implicated four inner helical phenylalanines near the cytoplasmic side as a possible locus of the channel gate. In the present study, we investigate whether this structural feature corresponds to the physiological pH gate of the renal inward rectifier, Kir1.1 (ROMK, KCNJ1). Kir1.1 is endogenous to the mammalian renal collecting duct and the thick ascending limb of Henle and is strongly gated by internal pH in the physiological range. It has four leucines (L160-Kir1.1b), homologous to the phenylalanines of KirBac1.1, which could function as steric gates near the convergence of the inner (M2) helices. Replacing these Leu-160 residues of Kir1.1b by smaller glycines abolished pH gating; however, replacement with alanines, whose side chains are intermediate in size between leucine and glycine, did not eliminate normal pH gating. Furthermore, a double mutant, constructed by adding the I163M-Kir1.1b mutation to the L160G mutation, also lacked normal pH gating, although the I163M mutation by itself enhanced the pH sensitivity of the channel. In addition to size, side-chain hydrophobicity at 160-Kir1.1b was also important for normal pH gating. Mutants with polar side chains (L160S, L160T) did not gate normally and were as insensitive to internal pH as the L160G mutant. Hence, either small or highly polar side chains at 160-Kir1.1b stabilize the open state of the channel. A homology model of the Kir1.1 closed state, based on the crystal structure of KirBac1.1, was consistent with our electrophysiological data and implies that closure of the Kir1.1 pH gate results from steric occlusion of the permeation path by the convergence of four leucines at the cytoplasmic apex of the inner transmembrane helices. In the open state, K crosses the pH gate together with its hydration shell.